The Implementation of Student Worksheet Based on Problem Based Learning on Environmental Changes to Train Critical Thinking Skill for Students of Grade X Senior High School - Dewi, Lailia Kurniawati; Kuntjoro, Sunu (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2024)
Abstract One of the characteristics of the Independent Curriculum listed in the Pancasila Student Profile dimension is critical reasoning. This is in line with the demands of 21st-century skills, namely critical thinking. The implementation of the Independent Learning Curriculum emphasizes the selection of learning models. One of the learning alternatives that can be implemented is learning that applies LKPD based on Problem Based Learning (PBL) to train students' critical thinking skills in class X environmental change materials adapted from the LKPD developed by Afkarina (2023). The objective of this study is to describe 1) the implementation of learning, 2) students' critical thinking skills, and 3) students' responses. This research includes a type of application research with a Pre-experimental design, the research target is 98 students in class X of SMAN 1 Pesanggaran, Banyuwangi. The parameters measured were 1) the implementation of learning, 2) students' critical thinking skills, and 3) students' responses. Research instrument was obtained from validation, critical thinking skills observation sheet, questionnaire and test sheets. The data from the research results were analyzed using a quantitative descriptive analysis method. The results of the study showed that 1) the implementation of learning carried out by teachers was very good with a score of 99.44%, 2) 95.19% of students had carried out critical thinking skills very well and achieved the completeness of indicators, 3) the response of students to LKPD was 95.69% or very positive. Keywords: the implementation of student woorsheets based on problem based learning, critical thinking skills, environmental change material. Abstrak Salah satu karakteristik dalam Kurikulum Merdeka yang tercantum dalam dimensi Profil Pelajar Pancasila adalah bernalar kritis. Hal ini selaras dengan tuntutan keterampilan abad ke-21 yaitu berpikir kritis. Implementasi Kurikulum Merdeka Belajar menekankan pada pemilihan model pembelajaran. Salah satu alternatif pembelajaran yang dapat diimplementasikan yaitu pembelajaran yang menerapkan LKPD berbasis Problem Based Learning (PBL) untuk melatihkan keterampilan berpikir kritis peserta didik pada materi perubahan lingkungan kelas X yang diadaptasi dari LKPD yang dikembangkan Afkarina (2023). Tujuan penelitian ini untuk mendeskripsikan 1) keterlaksanaan pembelajaran, 2) keterampilan berpikir kritis peserta didik, dan 3) respon peserta didik. Penelitian ini termasuk jenis penelitian penerapan dengan desain Pre-eksperimental, sasaran penelitian 98 siswa kelas X SMAN 1 Pesanggaran, Banyuwangi. Parameter yang diukur yaitu 1) keterlaksanaan pembelajaran, 2) keterampilan berpikir kritis peserta didik, dan 3) respon peserta didik. Intrumen penelitian ini diperoleh dari lembar keterlaksanaan, lembar observasi keterampilan berpikir kritis, lembar angket, dan lembar tes. Data hasil penelitiannya dianalisis mempergunakan metode analisis deskriptif kuantitatif. Hasil penelitian menunjukkan 1) keterlaksanaan pembelajaran yang dilaksanakan oleh guru sangat baik dengan skor 99,44%, 2) 95,19% peserta didik sudah menjalankan keterampilan berpikir kritis dengan sangat baik dan mencapai ketuntasan indikator, 3) respon peserta didik terhadap LKPD sebesar 95.69% atau sangat positif. Kata kunci: penerapan lembar kegiatan siswa berbasis problem based learning, keterampilan berpikir kritis, materi perubahan lingkungan.